Critical Philosophical Concept Analysis A Search for Meaning of the Concept Criticality in Adult Education - Bernadine W. Raiskums (Adult Education Research Conference, 2010)
This study applied philosophical concept analysis as a qualitative research method to study meanings of the concept “criticality” in adult education. The research design combined elements of two previously applied approaches emphasizing comprehensive and rigorous analysis of the literature. Results of this study provide a clear conceptual foundation and working definition for the concept “criticality” that will serve as a heuristic for further research, theory building, and practice.